Sulfur-, nitrogen- and platinum-doped titania thin films with high catalytic efficiency under visible-light illumination - Žener, Boštjan; Matoh, Lev; Carraro, Giorgio; Miljević, Bojan; Cerc Korošec, Romana (Beilstein Journal of Nanotechnology, 2018)
Titanium dioxide photocatalysts have received a lot of attention during the past decades due to their ability to degrade various organic pollutants to CO2 and H2O, which makes them suitable for use in environmental related fields such as air and water treatment and self-cleaning surfaces. In this work, titania thin films and powders were prepared by a particulate sol–gel route, using titanium tetrachloride (TiCl4) as a precursor. Afterwards, the prepared sols were doped with nitrogen (ammonium nitrate, urea), sulfur (thiourea) and platinum (chloroplatinic acid), coated onto glass substrates by dip-coating, and thermally treated in a muffle furnace to promote crystallization. The resulting thin films were then characterized by various techniques (i.e., TGA-DSC-MS, XRD, BET, XPS, SEM, band gap measurements). The photocatalytic activity of the prepared thin films was determined by measuring the degradation rate of plasmocorinth B (PB), an organic pigment used in the textile industry, which can pose an environmental risk when expelled into wastewater. A kinetic model for adsorption and subsequent degradation was used to fit the experimental data. The results have shown an increase in photocatalytic activity under visible-light illumination of nonmetal and metal doped and co-doped titania thin films compared to an undoped sample.
Keywords: doping; photocatalysis; sol–gel synthesis; thin films; titanium dioxide; visible-light illumination